Clinical Study on the Effects of Multi-Parameter “Yi-Zhi-Chan” (One-Finger Wrap) Manipulation on Myofascial Trigger Points of the Upper Trapezius Muscle in NTCS - Bian, Shuai; Yuan, Haiguang (Journal of Contemporary Medical Practice, 2026)
Objective: To investigate the effects of the “Yi-Zhi-Chan” (One-Finger Wrap) manipulation and conventional Tuina therapy on upper trapezius myofascial trigger points in patients with non-specific neck pain (NTCS), and to evaluate the clinical value of the two techniques using multidimensional parameters. Methods: A total of 64 NTCS patients with upper trapezius trigger points who met the inclusion criteria were enrolled. Patients were randomly assigned, using a random number table, into the observation group receiving “Yi-Zhi-Chan” manipulation (n = 32) and the control group receiving conventional Tuina therapy (n = 32). Both groups underwent their respective interventions once daily, with a 30-minute interval between treatments, for a total of 10 sessions per treatment course. Outcomes were assessed before and after the intervention, including the Short-Form McGill Pain Questionnaire (SF-MPQ), Neck Disability Index (NDI), trapezius trigger point fascia thickness, Young’s modulus, and shear wave velocity. Clinical data were collected via case report forms, and statistical analyses were performed using SPSS 27.0 to evaluate the efficacy of “Yi-Zhi-Chan” manipulation and to compare its clinical effects with conventional Tuina. Results: After one treatment course, in the observation group, 5 patients were cured, 17 showed marked improvement, 8 showed improvement, and 2 showed no effect, resulting in a total effective rate of 93.75%. In the control group, 4 patients were cured, 18 showed marked improvement, 6 showed improvement, and 4 showed no effect, with a total effective rate of 87.50%. Statistical analysis showed no significant difference between the two groups (P = 0.391 > 0.05). Conclusion: Both “Yi-Zhi-Chan” manipulation and conventional Tuina therapy effectively improve clinical symptoms in NTCS patients. However, the clinical efficacy of “Yi-Zhi-Chan” manipulation appears superior to that of conventional Tuina.